If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9.1m + -5.2 = 3.1m + 13.4 Reorder the terms: -5.2 + 9.1m = 3.1m + 13.4 Reorder the terms: -5.2 + 9.1m = 13.4 + 3.1m Solving -5.2 + 9.1m = 13.4 + 3.1m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3.1m' to each side of the equation. -5.2 + 9.1m + -3.1m = 13.4 + 3.1m + -3.1m Combine like terms: 9.1m + -3.1m = 6m -5.2 + 6m = 13.4 + 3.1m + -3.1m Combine like terms: 3.1m + -3.1m = 0.0 -5.2 + 6m = 13.4 + 0.0 -5.2 + 6m = 13.4 Add '5.2' to each side of the equation. -5.2 + 5.2 + 6m = 13.4 + 5.2 Combine like terms: -5.2 + 5.2 = 0.0 0.0 + 6m = 13.4 + 5.2 6m = 13.4 + 5.2 Combine like terms: 13.4 + 5.2 = 18.6 6m = 18.6 Divide each side by '6'. m = 3.1 Simplifying m = 3.1
| 14x^2+29-15= | | 10y=3(y+7) | | 2x^2+7x+5= | | 1x^3-12x+35= | | x^3-12x+35= | | 3(y+5)=8y | | -2x^3-2x^2+12x= | | -9*-9= | | 4*2*-9= | | 7(c-2)-6c=2(c-10)+10 | | 2x^2+15x+25= | | 5x-7=2x+11 | | 5x+8y=12 | | 20(s-9)-13=100+19(s+1) | | (r-11)+2r-6=11r(1) | | 5x^2-16x+12= | | 11(4e-1)-34e=9(e-1)-11 | | 7x-3=5(x-9) | | y=-3x^2-1 | | 12(x-1)=8(x+1) | | 6z-9+2z=7(z-2)-4 | | -2(h-7)=3(2h+14) | | x^2+7x+10x= | | 24c-11=-4c+7-10c | | -18y=396 | | -x^2-2x+48= | | 7p+5=6p-5-9p-1 | | 5x^2-9x=2 | | 14(x-10)-10x=3(x-2)+1 | | 3x^2+27x+60= | | -4(x-5)=8 | | 5y=10 |